Significance of Electrocardiographic Changes in Hypertension. Issue 5636 (11th January 1969) - Hamer, John; Shinebourne, Elliot; Fleming, James
Abstract : Studies in 17 hypertensive patients showed that the electrocardiographic features of T-wave inversion and S–T segment depression distinguish those patients with higher systolic blood pressures. They do not indicate impaired cardiac function.